(untitled) (Journal of Human Sciences, 2022)
The study of ‘ Anna’ is usually done in two chapters of Arabic grammar books which are: condition and interrogative. In this paper, its position in the Holly Qur’an was tracked , and the results showed that it was used only once as condition and that what Arab scholars assured. For this reason the researcher focused on the interrogative ‘ ‘Anna’ and she used the analytical method for this study in order to know its properties and its contextual connotations in the Holly Qur’an. The research was divided into two parts; the first was a theoretical study about the interrogative ‘ Anna’. This part started by defining the interrogative and mentioning its famous words and its rhetorical purposes. Also, it aimed to study ‘Anna’ and its meaning and its grammatical analysis in order to analyze its sentence anywhere in the Holly Qur’an, and to present scholars’ points of views about its grammatical analysis in the second part of this paper. The results showed that ‘Anna’ was used for the figurative question in most of its positions in the Holy Quran for the contextual rhetorical purposes; and It’s sentence system was limited only to three patterns. The context also referred that it has a general indication which used to express something that has different aspects. Based on the results, the researcher suggested that ‘Anna’ should be analyzed as an adverb to achieve the compatibility between its grammatical and connotation function in the context, and to bridge any shortcoming might affect the meaning as it was presented before. At the end, the results and the recommendations of the research were presented.